2015
DOI: 10.1371/journal.pone.0129383
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on the Safety of Vascular Endothelial Growth Factor (VEGF) Inhibitors for the Treatment of Retinopathy of Prematurity

Abstract: IntroductionLaser photocoagulation is the current gold standard treatment for proliferative retinopathy of prematurity (ROP). However, it permanently reduces the visual field and might induce myopia. Vascular endothelial growth factor (VEGF) inhibitors for the treatment of ROP may enable continuing vascularization of the retina, potentially allowing the preservation of the visual field. However, for their use in infants concern remains. This meta-analysis explores the safety of VEGF inhibitors.MethodsThe Ovid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 108 publications
0
55
0
Order By: Relevance
“…Several clinical studies have documented the use of anti‐VEGF therapy to tackle the neovascular phase of ROP . A generally favourable outcome was detected in the majority of the reports, but in some of the studies, adverse effects, such as endophthalmitis, haemorrhage, retinal detachment and cataract, were also reported .…”
Section: Therapies and Prevention Of Ropmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have documented the use of anti‐VEGF therapy to tackle the neovascular phase of ROP . A generally favourable outcome was detected in the majority of the reports, but in some of the studies, adverse effects, such as endophthalmitis, haemorrhage, retinal detachment and cataract, were also reported .…”
Section: Therapies and Prevention Of Ropmentioning
confidence: 99%
“…A generally favourable outcome was detected in the majority of the reports, but in some of the studies, adverse effects, such as endophthalmitis, haemorrhage, retinal detachment and cataract, were also reported . The main advantages of anti‐VEGF therapy over the use of laser include the following: easier administration under topical anaesthesia and preservation of visual field and lower rates of myopia . However, a number of disadvantages have emerged during its use in clinical or animals models.…”
Section: Therapies and Prevention Of Ropmentioning
confidence: 99%
“…Fundus laser photocoagulation and intravitreal injection of anti VEGF drugs were the main therapies, but both have certain side effects: Fundus laser treatment can cause certain damage to retina and irreversible damage to children's peripheral vision. Intravitreal injection of anti VEGF drugs may lead to endophthalmitis and traumatic cataract, when anti VEGF drugs enter the blood circulation, it will affect the development of blood vessels in other organs, especially the brain, lung and kidney [3,24]. Moreover, these two therapies are not effective in all ROP cases, and the search for therapeutic drugs for phase I ROP has become a hot spot in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Most systemic complications were thought to be incidental and not caused by anti-VEGF injection. Overall, the meta-analysis concluded that anti-VEGF therapy has a low-risk profile in ROP treatment in the first 6 months [25].…”
Section: Adverse Outcomesmentioning
confidence: 95%